european-style conversion - Grigoryeva, Elena (project baikal, 2018)
In the section “European-style conversion” there are two almost detective stories about transformation of prison castles into a new urban quarter (Germany) and a garden (Great Britain). The renovated German quarter was seamlessly integrated into the structure of the core of the imperial city thanks to the placing of education institutions in the historical building together with strengthening the trading function. The English garden became the embodiment of harmony between the old brick walls and the enfilade of green interiors. A long article by our permanent author from France, Christian Horn, reviews regeneration of industrial facilities and areas as an alternative to building on Greenfield. In the present-day postindustrial Europe (including Russia) conversion often looks like a far-seeing and cost-effective policy.The section is culminated by a largescale example of conversion of industrial facilities in Khamovniki, downtown Moscow. The object of the issue is a weaving factory “Red Rose” transformed into a contemporary multifunctional complex. Its history that is as long as a quarter of the millennium coexists with Yandex information technologies, while the permeability of the renewed quarter improves the level of adjoining streets.